2021
DOI: 10.1038/s41586-021-03807-6
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RBD antibodies that maximize breadth and resistance to escape

Abstract: An ideal anti-SARS-CoV-2 antibody would resist viral escape [1][2][3] , have activity against diverse SARS-related coronaviruses (sarbecoviruses) [4][5][6][7] , and be highly protective through viral neutralization [8][9][10][11] and effector functions 12,13 . Understanding how these properties relate to each other and vary across epitopes would aid development of antibody therapeutics and guide vaccine design. Here, we comprehensively characterize escape, breadth, and potency across a panel of SARS-CoV-2 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
532
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 461 publications
(601 citation statements)
references
References 115 publications
36
532
0
Order By: Relevance
“…We demonstrate here that S309, the parent mAb of sotrovimab which has received an emergency use authorization from the FDA, is unaffected by antigenic drift observed in variants of concern and interest due to recognition of a conserved RBD epitope (12,15,56). The recent discovery of multiple additional conserved antigenic sites recognized by RBD-specific mAbs with (near) pan-sarbecovirus neutralizing activity (16,17,21,(73)(74)(75) and the anticipated continued emergence of SARS-CoV-2 variants motivate the clinical development and deployment of some of these mAbs for prophylaxis with at-risk patients and for treatments of unvaccinated individuals or breakthrough infections. Moreover, next-generation vaccine candidates have recently been described to elicit broad sarbecovirus immunity (41,76,77), holding the promise to be resilient to the emergence of SARS-CoV-2 variants and of new zoonotic sarbecoviruses.…”
Section: And Biolayer Interferometry (Fig 2i Fig S4x Tablementioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrate here that S309, the parent mAb of sotrovimab which has received an emergency use authorization from the FDA, is unaffected by antigenic drift observed in variants of concern and interest due to recognition of a conserved RBD epitope (12,15,56). The recent discovery of multiple additional conserved antigenic sites recognized by RBD-specific mAbs with (near) pan-sarbecovirus neutralizing activity (16,17,21,(73)(74)(75) and the anticipated continued emergence of SARS-CoV-2 variants motivate the clinical development and deployment of some of these mAbs for prophylaxis with at-risk patients and for treatments of unvaccinated individuals or breakthrough infections. Moreover, next-generation vaccine candidates have recently been described to elicit broad sarbecovirus immunity (41,76,77), holding the promise to be resilient to the emergence of SARS-CoV-2 variants and of new zoonotic sarbecoviruses.…”
Section: And Biolayer Interferometry (Fig 2i Fig S4x Tablementioning
confidence: 99%
“…The S2 subunit contains the fusion machinery and undergoes large-scale conformational changes to drive fusion of the virus and host membranes (14), enabling genome delivery and initiation of infection. Abs that bind to specific sites on the RBD (15)(16)(17)(18)(19)(20)(21)(22), the NTD (23)(24)(25)(26), or the fusion machinery stem helix (27)(28)(29)(30)(31) interfere with receptor attachment or membrane fusion. Serum neutralizing Ab titers are a correlate of protection against SARS-CoV-2 in non-human primates (32)(33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 A recent massive analysis of more than 300,000 viral genomes has suggested that mutations within the S protein represent one of the main pathways of adaptive evolution in SARS-CoV-2, 8 thereby raising concerns about potential for resistance to neutralizing antibodies acquired through either vaccination or previous COVID-19 infection. [9][10][11] Recent developments have supported the concept of "inescapable" monoclonal antibodies with broad activity against multiple variants of SARS-CoV-2 12 ; however the ongoing genetic evolution of the virus raises uncertainty regarding the possibility of new viral mutations that allow immune escape. Moreover, given that some proportion of the viral mutations may also alter infectivity, disease severity, interaction with host immunity, and resistance to antiviral drugs, 13 both the World Health Organization (WHO) 14 and the United States Centers for Disease Control & Prevention (CDC) 15 have actively been monitoring at least 21 new variants of SARS-CoV-2.…”
Section: Mainmentioning
confidence: 99%
“…26 Collectively, these empirical results suggest that C662-C671 epitope might represent a privileged motif for vaccine development and perhaps even a potential target for inescapable antibodies. 12 To gain further insight into the structural properties of C662-C671, we performed comparative structural analysis (Fig. 1b) and molecular simulations (Fig.…”
Section: Mainmentioning
confidence: 99%